P0649MAY HIGH CUT-OFF HAEMODIALYSIS STILL BE CONSIDERED BENEFICIAL IN THE TREATMENT OF ACUTE KIDNEY INJURY RELATED TO MULTIPLE MYELOMA?. (6th June 2020) - ALEXANDRU, SIMONA; López Picasso, Maria; García-Puente Suarez, Laura; Pizarro Sanchez, Maria Soledad; Pampa Saico, Saul; Poma Tapia, Marisol; Barba, Raquel
Abstract: Background and Aims: Almost 20% of the patients with multiple myeloma (MM) associate renal involvement, and 5% need long-term haemodialysis treatment. Both plasmapheresis and high cut-off haemodialysis (HCO-HD) have been used to remove light chains from the blood and minimize the renal damage. In the largest study, plasmapheresis has been shown to be ineffective in the renal recovery. Furthermore, the most important trial, EuLITE II, concluded that HCO-HD did not improve renal recovery and independence from haemodialysis. The hypothesis of this work is that patients with an acute renal failure related to multiple myeloma undergoing early HCO-HD treatment, before being haemodialysis-dependent, may achieve better renal function in short and, perhaps, in long term. Method: We have studied five patients with multiple myeloma and acute renal failure who received treatment with HCO-HD in order to remove serum kappa or lambda light chains. The procedure was realized with Filtryzer BK2.1F dialyzer (Palex Medical) with an area of 2.1 m 2 at a blood flow of 250 ml/min and a dialysate flow of 500 ml/min, usually changing the dialyzer in the middle of the session. The sessions lasted between 6 and 8 hours, initially on successive days, and alternate days afterwards. Results: Between July 2016 and November 2019, five patients with a mean age of 67.8 years (2 women and 3 men) received HCO-HD. Three of them had MM with lambda light chains, and two of them had MM with kappa light chains. The average bone marrow plasmocytosis was 38.6 % (minimum 10% and maximum 90%). Two patients required treatment with haemodialysis for glomerular filtrate (FG) estimated by MDRD-4 formula of 4 and 5 ml/min, respectively. The other three had a GF (MDRD-4) between 19 and 30 ml/min. Initial hematological treatment included bortezomib, dexamethasone, and thalidomide. One patient was switched to carfilzomib. Only two patients underwent renal biopsy, both showing myeloma kidney with intratubular light chain casts. An average of 9.8 sessions has been administered (minimum 5, maximum 19). At the end of the treatment, serum kappa light chains decreased from a mean of 29461 mg/L to 1516.5 mg/L, and serum lambda chains decreased from a mean of 7245 mg/L to 1030.66 mg/L. At the beginning of the treatment the mean GF (MDRD-4) was 17.4 ml/min, 29.6 ml/min at the end of it, and 42.33 ml/min six months later (table 1). Only one patient became dependent of haemodialysis. This patient developed renal failure in context of a second relapse of a very aggressive myeloma. Another patient who presented 47900 mg/L of serum kappa light chains at diagnosis, 90% bone marrow plasmocytosis, and a GF (MDRD-4) of 30 ml/min when started HCO-HD, in the present and few days after 19 sessions has a GF (MDRD) of 43 ml/min. Conclusion: An early treatment with HCO-HD, before the patients need renal replacement therapy, may lead to a better renal outcome and independence from haemodialysis at least in the medium term. Largest studies are necessary to confirm this hypothesis.